2020
DOI: 10.4081/ejh.2020.3142
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor intervention to reduce myocardial injury and improve cardiac function on diabetic myocardial infarction rats

Abstract: Acute myocardial infarction (AMI) is recognized to be a severe threat to people’s health conditions and life quality. The accumulation of hepatocyte growth factor (HGF) in ischemic myocardium has been observed in both processes of experimental ischemia and reperfusion (I/R) and permanent coronary artery occlusion. The aim of the study was to investigate the effect of HGF on myocardial cell apoptosis, ventricular remodeling and cardiac function after myocardial infarction (MI) in diabetic rats, and to explore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In terms of cell survival and tissue regeneration, HGF is one of the most potent cell mitotic factors and a critical component of tissue wound repair [ 25 ]. HGF intervention has been shown to reduce tissue damage and improve cardiac function [ 26 , 27 ]. In our study, we showed that SCS transplantation induced HGF expression in MI tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cell survival and tissue regeneration, HGF is one of the most potent cell mitotic factors and a critical component of tissue wound repair [ 25 ]. HGF intervention has been shown to reduce tissue damage and improve cardiac function [ 26 , 27 ]. In our study, we showed that SCS transplantation induced HGF expression in MI tissue.…”
Section: Discussionmentioning
confidence: 99%